Amine unit corrosion in refineries - Harston, J. D. (Publications (European Federation of Corrosion) ;, 2007)
The corrosion of carbon steels in amine units used for gas treatment in refining operations is a major problem for the petrochemical industry. Maximising amine unit reliability, together with improving throughput, circulation and treatment capacity, requires more effective ways of measuring and predicting corrosion rates. However, there has been a lack of data on corrosion. This valuable report helps to remedy this lack of information by summarising findings from over 30 plants. It covers such amine types as methyl diethanolamine (MDEA), diethanolamine (DEA), monoethanolamine (MEA) and di-isopropanolamine (DIPA), and makes recommendations on materials and process parameters to maximise amine unit efficiency and reliability. Covers such amine types as Methyl Diethanolamine (MDEA) and Di-isopropanolamineMakes recommendations on materials and process parameters to maximise amine unit efficiency and reliability.